Standard Operating Procedure (SOP) for DNA extraction - Olutegbe, A.; Nnadi, A.; Mbanjo-Edwige, G.; Rabbi, I. (International Institute of Tropical Agriculture, 2024)
Deoxyribonucleic acid (DNA) extraction is an important process in molecular plant breeding. DNA extraction involves isolating DNA from the nucleus of a cell. Once purified, scientists can study individual genes, sequence the entire genome, modify sections of DNA, among others.